a Critical Analysis of the Implementation of Deep Learning Policy at Elementary School Level in Indonesia - Fahmi Imron, Ilmawati; Hadi, Syamsul; Dewi, Radeni Sukma Indra (Universitas Negeri Padang, 2025)
This study critically examines the implementation of the Deep Learning policy in Indonesian elementary schools by comparing the directives of Permendikdasmen No. 13 of 2025 with empirical findings from a systematic literature review. The review explores how the policy’s vision of mindful, meaningful, and joyful learning aligns with classroom realities. Using a structured analysis of selected studies published between 2020 and 2025, the findings reveal persistent gaps between policy expectations and practice, including limited teacher understanding, inconsistent implementation, and inadequate infrastructure, particularly in rural contexts. These gaps hinder the development of critical thinking, creativity, collaboration, and reflective learning that the policy envisions. The study concludes that strengthening teacher competence, improving school support systems, and ensuring equitable digital infrastructure are essential for achieving meaningful implementation. Readers are encouraged to reflect on how systemic alignment can transform policy intentions into genuine learning experiences.